The Attractiveness Of Muhammad Yusuf's Poetry - Ma'rifatov Khursandbek (Zien Journals, 2023)
Muhammad Yusuf, who was born in a simple peasant family, entered the world of creativity and the spiritual and spiritual significance of his creative works in human life.
Keywords: Muhammad Yusuf; artistic analysis of his poetry; his achievements